﻿Pharmacists' attitudes to dispensing food supplements to chronically ill patients: a pilot survey among community pharmacies in Bulgaria - Antoaneta Balkanska-Mitkova; Antoniya Yaneva; Magdalena Kondeva-Burdina; Maria Dimitrova (Pensoft Publishers, 2022)
Background: Within the last years, excessive utilization of food supplements for prevention and prophylaxis in different chronic diseases is observed. In order to extend the control on the arrangement of the market, utilization, and safety of food supplements, the European Commission took genuine regulatory steps to harmonize the criteria for FS and to guarantee that they are not giving deceiving information. However, excessive use, uncontrolled patients consumption, exposure to higher than recommended intakes, and even interaction with specific medicines can cause toxicity risks and pose serious health concerns. The aim of this study is to examine the tendency of pharmacists to correctly recommend food supplements to chronically ill patients in order to extend the pharmaceutical care and prevent side effects. Materials and methods: The used method is an anonymous survey that was conducted by using the direct questionnaire method among master pharmacists and assistant pharmacists working in community pharmacies in Bulgaria. Results: The results show that the majority of the pharmacists are willing to recommend food supplements and that they could participate in the monitoring of chronically ill patients with food supplements intake. On the other side, the survey shows that most of the patients are seeking for food supplements and do ask for advice. Conclusion: In conclusion, pharmacists as the most accessible health care professionals can provide more detailed information concerning food supplements in order to avoid negative effects on the safety of chronically ill patients, especially with additional training in the field.